The JKN Participants’ Experience on the BPJS Service in Malang Indonesia - Sunardi Sunardi; Faqih Ruhyanuddin (University of Muhammadiyah Malang, 2018)
The cost of health services at the felt by middle-down economic community still expensive makes them very difficult to achieve the welfare of health. The Government issued a policy Jaminan Kesehatan Nasional (JKN) held through the mechanism of social health insurance that is compulsory (mandatory). Research methods used in this research is descriptive-qualitative design in depth-interviews. This research was conducted in Primary Clinic of Malang Dinoyo and Griya Melati Diagnostic Malang with 10 participants who have become participants Purposive Sampling techniques through JKN. Data analysis techniques using data analysis techniques Colaizzi. The results of the interviews conducted on participants is diidentifikasinya 6 themes, namely 1) problems in the service of JKN; 2) Excess JKN within health services; 3) Service to use JKN got equal treatment; 4) Program JKN only bear the costs of the treatment in part only; 5) expectations to JKN; 6) Transition Askes became member of the BPJS. The experience of the participants against BPJS majority is very helpful in the Ministry of health. There are some participants who are not satisfied will the performance of the Basic program and hope the BPJS would be even better in providing health services. Based on these studies are recommended for the Government to be proactive in supervising and evaluating the course of program BPJS.